Microwave-assisted Synthesis of Bioactive Six-membered O-heterocycles - De, Aramita; Sarkar, Subhankar; Majee, Adinath (Current Microwave Chemistry, 2023)
Microwave radiation has been utilised since the late 1970s as an alternative thermal energy source for chemical reactions. Initially used in inorganic chemistry, its potential for organic chemistry was revealed in 1986. Convertion of electromagnetic energy into heat, with frequencies ranging from 0.3-300 GHz using microwave irradiation, is an efficient heating method. The microwave heating method has significant potential for industrial processes, reducing reaction times and enhancing yields and selectivity. It finds applications in peptide and organic synthesis, materials science, polymer chemistry, biochemical processes, and nanotechnology. Microwave-assisted organic synthesis is environmentally friendly and beneficial for producing bioactive heterocyclic compounds. Oxygen-containing heterocycles are abundant and possess various biological functions, making them essential for developing new drugs. Microwave technology facilitates the synthesis of these compounds, including bioactive six-membered o-heterocycles such as pyrones, oxazolones, furanones, oxetanes, oxazolidinones, and dioxetanes. By utilizing modern organic transformations, microwave-assisted chemistry enhances the efficiency of synthetic processes, leading to the discovery of more beneficial molecules. The review provides an up-to-date analysis of the synthesis and medicinal properties of O-heterocycles, emphasizing the strengths and needs of this field. It guides researchers, facilitating microwave-assisted green synthesis reactions and offering a flexible platform for forming bioactive heterocyclic rings.
Keywords: six-membered